(untitled) (Sains Humanika, 2017)
This study entitled â€œAnalysis of the Novel Leftenan Adnan Wira Bangsa work Abdul Latip bin Talibâ€ with the objective to study the thinking of the author in his work which is related to the events he undertook as well as though the experiences of other individual that are adapted in this novel. This study uses a local thory of Integrated System theory 4K or short name SPB4K introduced by Mohd Yusof Hasan. This theory is based on the philosophy of unity of thought which is thought thinking, spiritual thingking, scientific thinking and creativity thinking. In addition the study is performed to identify the authorâ€˜s mind and to analyse the author thought using the SPB4K theory. From the research done, it is concluded that all four aspect of thinking are widely used in the novel Leftenan Adnan Wira Bangsa and until now, there is no research done on it. This may due to the fact that this is a 2014 novel and it is just introduced to Form 4 to study for Zone 2 in Malaysia. This research also is expected to pull the author interest to produce more quality literature works and become the compulsory KOMSAS text for schools in Malaysia. Apart from that, this literature can eleviate the nation dignity and become the example to the society.